Screening of wheat germplasm for their susceptibility against different seedling diseases (Bangladesh Journal of Agricultural Research, 2010)
Fifteen wheat germplasm, namely BAW-1033, BAW-l045, BAW-1056, BAW1061, BAW-1064, BAW-1004, BAW-l008, BAW-1027, BAW-1035, Sonalika, Gourob, Protiva, Shatabdi, Sourov and Kanchan (check) were screened against different seedling diseases in two consecutive years under inoculated condition. Before sowing, the soils of the experimental field were inoculated with five fungal pathogens, namely Sclerotium rolfsii, Biplaris sorokiniana, Fusarium oxysporum, Pythium aphanidermatum, and Rhizoctonia solani. Considering the lower percent of diseased seedling and higher vigour index, four wheat germplasrn, namely Shatabdi, BAW-1045, BAW-1004 and Protiva were selected as tolerant materials against seedling diseases. Key Words: Screening; wheat germplasm; seedling diseases DOI: 10.3329/bjar.v34i4.5842Bangladesh J. Agril. Res. 34(4) : 673-681, December 2009